Knowledge of students in the Technical Nursing course on basic life support (Research, Society and Development, 2021)
Introduction: Knowledge about Basic Life Support (BLS) can save lives. Objective: To evaluate the knowledge of students in the technical course in nursing before and after theoretical training on BLS in adults. Materials and Methods: Quasi-experimental study carried out with 74 students of the technical nursing course at an educational institution in Minas Gerais. The measurement of sociodemographic variables and knowledge about BLS was carried out using a previously validated questionnaire. Using the IBM ® SPSS 23.0 software, the Mcnenar and Wilcoxon tests were used to compare the proportion of correct answers and the median level of knowledge. Results: The median knowledge of students after training was significantly higher than in the pre-test (p